Automated cheque clearing system: tools and practices in Shahjalal Islami Bank Limited - Mamun, Abdullah Al (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.